INTERACT AND REACT: GENDER, OPEN-SOURCE SOFTWARE, AND THE GOVERNANCE OF USER INTERFACE TECHNOLOGIES - Brooke, Siân (AoIR Selected Papers of Internet Research, 2026)
Discussions of gender diversity in open-source software (OSS) often focus on increasing women’s participation rather than questioning how their contributions shape development itself. This study examines $2 , a widely used tool for building websites and applications, to explore gendered patterns in contribution over 11 years (2013–2024). Using data from GitHub, a dominant platform for software collaboration, I analyze who contributes to different aspects of the project and how participation shifts around major software updates.Findings show that women’s contributions are concentrated on improving existing features and maintaining project stability, $2 . Their exclusion is not just a matter of representation; it reinforces structural inequalities in whose labor is recognized and rewarded in digital infrastructure governance. By shifting the focus from simply counting participation to examining how gendered divisions of labor shape digital tools, this study highlights the need to $2 in the development of internet technologies.